CONTROL SYSTEMS classical, modern, and intelligent approaches. - Raol, J. R. (Jitendra R.), 1947- ([S.l.] : CRC PRESS, 2019)
Control Systems: Classical, Modern, and AI-Based Approaches provides a broad and comprehensive study of the principles, mathematics, and applications for those studying basic control in mechanical, electrical, aerospace, and other engineering disciplines. The text builds a strong mathematical foundation of control theory of linear, nonlinear, optimal, model predictive, robust, digital, and adaptive control systems, and it addresses applications in several emerging areas, such as aircraft, electro-mechanical, and some nonengineering systems: DC motor control, steel beam thickness control, drum boiler, motional control system, chemical reactor, head-disk assembly, pitch control of an aircraft, yaw-damper control, helicopter control, and tidal power control. Decentralized control, game-theoretic control, and control of hybrid systems are discussed. Also, control systems based on artificial neural networks, fuzzy logic, and genetic algorithms, termed as AI-based systems are studied and analyzed with applications such as auto-landing aircraft, industrial process control, active suspension system, fuzzy gain scheduling, PID control, and adaptive neuro control. Numerical coverage with MATLAB is integrated, and numerous examples and exercises are included for each chapter. Associated MATLAB code will be made available.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / Mechanical; MATLAB; Automatic control; Automatic control -- Mathematical models; Control theory -- Computer programs